Recent advancement of fisetin-based nanoformulations in the management of psoriasis - Umesh B. Telrandhe; Anjum N. Hasnain; Sachin N. Kothawade; Darshan R. Telange (Discover Nano)
Abstract Psoriasis is a chronic inflammatory autoimmune skin disease with enhanced skin cell turnover. Despite the therapies currently available, better and target-oriented therapies are needed. Fisetin is a flavonoid with antioxidant, anti-inflammatory, and immunomodulatory properties. It shows therapeutic potential, but its poor bioavailability and penetration into the skin cannot be used effectively to treat psoriasis. While fisetin–loaded nanoformulations in cancer and other diseases have been explored, their potential as a therapy for psoriasis is unexplored. Most reviews detail the biological activities of fisetin or nanoformulations for psoriasis therapy but not their combination. The review here compiles fisetin’s chemical and pharmacological properties along with the problems with conventional drug delivery and fisetin-loaded nanoformulations such as polymeric nanoparticles, liposomes, solid lipid nanoparticles, nanogels, and micelles. It also discusses their mechanisms, preclinical results, and potential for the clinic. Preclinical studies demonstrate fisetin nanoformulations to enhance penetration into the skin, reduce inflammation, promote skin regeneration in psoriasis models, and alleviate symptoms of redness and scaling. Clinical trials are lacking, and studies are needed to assess safety and efficacy. Fisetin nanoformulations are a potential target-oriented psoriasis therapy with better drug delivery and fewer side effects than conventional therapies. Despite formulation stability, scalability, and regulatory issues, the potential for fisetin-loaded nanoformulations is excellent and needs further exploration for their safety and efficacy in patients. Graphical abstract